IPTEKS PROSES PENJUALAN MOBIL DI PT HASJRAT ABADI MANADO CABANG TENDEAN - Tumalun, Tommy L.H.; Triwellly, Dicky; Balau, Yehezkiel; Wokas, Heince R.N. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Industrial development in Indonesia is growing rapidly, especially in the automotive sector. PT Hasjrat Abadi is one of the automotive industries that is in great demand by the public, because PT Â Hasjrat Abadi always has innovation and quality in every product. PT Hasjrat Abadi holds Car and Motorcycle companies namely Toyota and Yamaha. PT Hasjrat Abadi Manado branch Tendean is a branch that has a strategic location, so many people buy cars in this branch. The process of purchasing a Car through a field sales or sales counter. Purchases can be made with cash or credit payments.Keywords: Automotive industry, innovation, product quality, sales, credit, and cash